Teachers’ and Students’ Perceptions of the Use of Animated Video Media in Fiqh Learning at Madrasah Salafiyah Wustha Ma'had Baitul Muhsinin Medari, Sleman - Nurul Hidayat; Dwi Sugiarto; Ramadhan, Rudi; Riky Supratama; Muhammad Shah Wildan (International Journal of Post Axial: Futuristic Teaching and Learning, 2026)
The integration of technology in fiqh learning in salafiyah madrasas faces challenges between maintaining traditional values and adopting modern learning media. This study aims to analyze the perceptions of teachers and students towards the use of animated video media in fiqh learning at Madrasah Salafiyah Wustha Ma'had Baitul Muhsinin Medari Sleman. Descriptive qualitative research with a case study approach, involving 1 fiqh teacher and 3 grade VIII students. Data were collected through in-depth interviews, participant observation, and documentation. Teacher perceptions show that animated videos greatly help visualize complex materials such as hajj pilgrimage and zakat, increase student learning motivation, and align with pesantren values. Students responded positively with high enthusiasm, better understanding, and improved memory retention of the material. Supporting factors include adequate technological infrastructure and management support, while obstacles include limited equipment and preparation requiring extra time. Animated video media effectively improves the quality of fiqh learning in salafiyah madrasas while maintaining traditional pesantren values.